Digital Ethnoscience: AR/VR Media Shaping Chemistry Learning in Indonesia - Tiara Lestari Paembonan; Varisky Abraham Dumanaw (Civiliza Publishing, Indonesia., 2026)
Chemistry learning still faces challenges due to the abstract nature of its concepts, particularly at the submicroscopic level, as well as the limited connection between subject matter and students’ everyday life contexts. Augmented reality (AR) and virtual reality (VR), on the other hand, offer interactive visualizations that can help students understand chemical concepts more concretely, while ethnoscience provides cultural context and local wisdom that make learning more meaningful. This article aims to analyze the trends, characteristics, and future directions of ethnoscience‑based AR/VR media in chemistry learning in Indonesia through a systematic literature review. The findings indicate that AR is more widely used than VR, especially for topics that require spatial visualization such as atomic structure, chemical bonding, molecular shapes, and virtual laboratories. Research on ethnoscience in chemistry education has also grown rapidly, particularly in improving chemical literacy and promoting contextual learning. However, the direct integration of ethnoscience‑based AR/VR remains limited. These findings highlight that the future development of chemistry learning media needs to balance technological aspects, conceptual accuracy, cultural relevance, and readiness for classroom implementation.